STUDENTS’ PERCEPTION TOWARD TEACHERS’ TEACHING STYLES AND THE USE OF LEARNING STRATEGIES IN TEACHING ENGLISH - Alfonsus Lamatokan (Makassar State University, 2018)
The aim of the study was to find out students’ perception toward teachers’ teaching styles and the use of learning strategies in teaching English. This study was conducted at SMA Negeri 1 Tobelo in all grades. The instrument used in the data collection was a questionnaire that consists of six indicators where these indicators refer to variables. The data were analyzed using Microsoft Excel and display in pie diagram. The finding indicates that the majority of students at SMA Negeri 1 Tobelo are aware that their teachers’ teaching styles and the use of learning strategies gave positive impact in do their learning. Their perception of their teachers’ teaching styles and learning strategies which covers attitudes, behavior, interaction, method, teaching material and media during teaching and learning process influenced the success of students in developing English skills. Most students of their conviction stated that their English teachers were responsible for their career as a good teacher. Thus, in doing them job, their awareness to make an effective teaching to support students’ success in learning English. Further studies might be conducted using interview to students to gain more information.